ON FUZZY SOFT GRAPHS - Akram, Muhammad; Nawaz, Saira (Italian Journal of Pure and Applied Mathematics, 2015)
Fuzzy sets and soft sets are two different soft computing models for representing vagueness and uncertainty. We apply these soft computing models in combination to study vagueness and uncertainty in graphs. We introduce the notions of fuzzy soft graphs, strong fuzzy soft graphs, complete fuzzy soft graphs, regular fuzzy soft graphs, and investigate some of their properties.